A Simple, Inexpensive Method for Mark-Recapture of Ixodid Ticks. Issue 6 (2nd November 2020) - White, Alexis; Minch, Robin; Bidder, Lindsey; Gaff, Holly
Abstract: Mark-recapture techniques have been widely used and specialized to study organisms throughout the field of biology. To mark-recapture ticks (Ixodida), we have created a simple method to mark ticks using nail polish applied with an insect pin secured in a pencil that allows for a variety of questions to be answered. For measuring tick control efficacy, estimating population estimates, or measuring movement of ticks, this inexpensive mark-recapture method has been easily applied in the field and in the lab to provide useful data to answer a variety of questions about ticks.